Correction: AlTawari et al. Nusinersen Treatment for Spinal Muscular Atrophy: Retrospective Multicenter Study of Pediatric and Adult Patients in Kuwait. Neurol. Int. 2024, 16, 631–642 - Asma AlTawari; Mohammad Zakaria; Walaa A. Kamel; Nayera Shaalan; Gamal Ahmed Ismail Elghazawi; Mohamed Esmat Anwar Ali; Dalia Salota; Amr Attia; Ehab Elsayed Ali Elanany; Osama Shalaby; Fatema Alqallaf; Vesna Mitic; et al. (Neurology International)
In the published publication [...]